2013
DOI: 10.1001/jamasurg.2013.2911
|View full text |Cite
|
Sign up to set email alerts
|

A Paradigm Shift in Trauma Resuscitation

Abstract: There has been a shift toward a reduced crystalloid volume and the recreation of whole blood from component products in resuscitation. These changes are associated with markedly improved outcomes and a new paradigm in the resuscitation of severely injured patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(32 citation statements)
references
References 29 publications
2
27
0
3
Order By: Relevance
“…13,14 However, in the context of current evidence, disparate strategies to guide MTPs exist. 14,15 Although a retrospective study comparing a TEG-guided MTPs to a historic cohort supports the use of TEG to guide MTPs, 37 this has not been prospectively validated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13,14 However, in the context of current evidence, disparate strategies to guide MTPs exist. 14,15 Although a retrospective study comparing a TEG-guided MTPs to a historic cohort supports the use of TEG to guide MTPs, 37 this has not been prospectively validated.…”
Section: Discussionmentioning
confidence: 99%
“…13 MTPs rely on abnormal values of CCA as triggers for transfusion of plasma, cryoprecipitate, and platelet units. 14 An alternative approach incorporates a VHA into MTPs to assess each stage of hemostasis, allowing for goal-directed treatment with blood products.…”
mentioning
confidence: 99%
“…Recently, there has been a shift toward reduced administration of crystalloid volume and use of blood products to achieve hemostasis and oxygen delivery while benefiting from the volume also provided by them. Kutcher et al (65) reported that systematization of such practices under an institutional MTP was associated with decreased blood product use, and when adjusting for age and injury characteristics, with a 5.6% reduction in mortality. MTPs are either based on fixed plasma:red blood cell (RBC), cryoprecipitate:RBC, and/or platelet (PLT):RBC ratios agreed upon institutions, or goal directed by viscoelastic point-of-care assays.…”
Section: Hemostasis Managementmentioning
confidence: 99%
“…The ratio of blood products at which this benefit is optimal remains a matter of debate. Based on recent data, what is certain is that coagulopathic trauma patients meeting criteria for massive transfusion benefit from early plasma and platelet administration, while being judicious with crystalloid administration (65). This benefit appears to be independent of the ratio of blood product used, as all studies that report improved outcomes with a particular ratio gave plasma and/or platelets earlier (68).…”
Section: Hemostasis Managementmentioning
confidence: 99%
“…Much of the focus of recent research has been on optimizing the ratio of blood product administration and minimizing the use of crystalloid. 1 However, it is the early and timely delivery of higher balanced ratios of plasma and platelets that allows for the achievement of the ultimate goal of DCR: the rapid restoration of circulating red cells, plasma proteins and platelets, while definitive control of bleeding is achieved. The protocolization of massive transfusion (MT) was developed with DCR and has been associated with decreased mortality, decreased multi-organ failure, and an overall decrease in the amount of product transfused.…”
Section: Introductionmentioning
confidence: 99%